Icarus - Icarus (Elsevier, 2026)
Icarus is devoted to the publication of original contributions in the field of Solar System studies. Manuscripts reporting the results of new research - observational, experimental, or theoretical - concerning the astronomy, geology, meteorology, physics, chemistry, biology, and other scientific aspects of our Solar System or extrasolar systems are welcome. The journal generally does not publish papers devoted exclusively to the Sun or the Earth; papers on celestial mechanics or astrophysics are acceptable only if they have a clear importance for planetary science; descriptive studies of meteorites should be addressed to journals of meteoritics, but are relevant for Icarus is they provide constraints on the formation or evolution of planetesimals, planets or the solar system in its globality. Icarus does not publish papers that provide "improved" versions of Bode's law, or other numerical relations, without a sound physical basis. Icarus does not publish meeting announcements or general notices. Reviews, historical papers, and manuscripts describing spacecraft instrumentation may be considered, but only with prior approval of the editor. An entire issue of the journal is occasionally devoted to a single subject, usually arising from a conference on the same topic. The language of publication is English. American or British usage is accepted, but not a mixture of these.
FI 0.69
Q2
Keywords: Physical Sciences & Engineering; Materials Science; Acuerdos transformativos; Transformative agreements; Interior terrestre; Geodinámica; Geodesia; Campo magnético terrestre; Estructura profunda